Arİf Pasha Mansion from its first construction to the present - Sedes, Fatma (Street Art & Urban Creativity, 2022)
Arif Pasha Mansion, where restoration works have been completed recently, is located in the Fatih district of Istanbul( İn old Eminönü). The building, which has been used with different functions since its construction, was first built as a mansion. It was now planned to be restored as the ''Provincial Youth Assembly and culture mansion'' by the Istanbul Metropolitan Municipality. It changed hands in 1911 and was used as ''Şehremaneti '' ( municipality building). It became the headquarters of the French occupation forces in 1918 and continued this function until 1923. Later it functioned as Turkey's first ''conservatory '' in the 1930s. In the following years, it began to be used as an official institution. This prepared text was created in order to explain the method followed in the project studies carried out regarding the building.